KEBERFUNGSIAN KELUARGA ANAK KORBAN EKSPLOITASI DI KECAMATAN TAMPAN KOTA PEKANBARU - Widya, Annisa; Umari, Tri; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: This research focuses on functions that exist in the family, such as biological functions, economic functions, educational functions, social functions, protection functions, recreation functions, and religious functions. And in research also find out about psychological problems, family integrity, and social relationships in the family. While the subjects in this study were children who were victims of exploitation located in Tampan District, Pekanbaru City. The study was conducted by obtaining qualitative and descriptive research types and the data obtained in the study were sourced from the results of structured observations and interviews. The results of the study were obtained by families who have not performed roles that are appropriate to their functions in a family. Apart from families that are not well scheduled, we also get the results of psychological conditions, family integrity and social conditions in the family that cause children to become victims of exploitation.Key Words: Family Function, Child Exploitation